(untitled) (Global Journal of Human-Social Science, 2024)
The migration scenario faces different conditions, with emphasis on the context of education and its repercussions on the individual’s life. Therefore, the general objective was to investigate the living conditions of migrant students in Brazil. An Integrative Literature Review was carried out, involving: elaboration of the guiding question; literature search and sampling; data collect; critical analysis of studies; discussion of results; and presentation of the integrative review. The results made it possible to select 8 studies using the inclusion and exclusion criteria. Subsequently, a framework was developed to record information based on the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" protocol. Five points were grouped: Education, Housing, Labor Market, Income and Health. Prior to this, the profile of the migrant population was created. Finally, the need to build policies and enforce rights to guarantee better living conditions for the migrant population was highlighted, in the fight against social inequality in the Brazilian context.